How Do Brazilian Software Development Teams Deal with Working From Home After a Year of the COVID-19 Pandemic? - Bezerra, Carla; Coutinho, Emanuel; Araujo, Amarildo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
The COVID-19 pandemic has lasted for over 1 year. During the pandemic, several software development companies migrated to working from home (WFH). Several studies have recorded an initial moment of adaptation to WFH. This study investigated how Brazilian software development teams dealt with WFH after 1 year of a pandemic and how this change in work was on the software development process. We applied a survey with 67 participants of software development teams and investigated aspects, as: work routine, collaboration, communication, productivity, financial assistance and software development process. We performed a quantitative and qualitative analysis of the survey results and compared them with previous studies. Our key findings are: (i) 56.71% of the participants said that it has an impact on the work routine related to work overload and exceeds the company’s standard hours; (ii) 92.54% of the participants consider their team to be collaborative; (iii) 82.70% are satisfied with the communication at WFH; (iv) 86.55% has meetings once or twice a day; (v) 59.7% had an improvement in productivity in WFH and 75% are satisfied with their productivity; (vi) 79.60% receive some assistance from the company for WFH; (vii) 82.1% said that the company intends or probably intends to continue in the WFH, and (viii) 55.2% said they had changed in the software development process due to WFH. The main positive changes in the process are related to the practices of: daily meetings, agile processes, code review, pair programming and code versioning.